2003
DOI: 10.1007/s00442-003-1427-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemical settlement inhibition versus post-settlement mortality as an explanation for differential fouling of two congeneric seaweeds

Abstract: It has been proposed that seaweed secondary metabolites, e.g. brown algal phlorotannins, may have an ecologically important function as a chemical defence against epiphytes, by acting against colonisation of epiphytic organisms. We tested whether the low epiphytic abundance on the invasive brown seaweed Fucus evanescens, compared to the congeneric F. vesiculosus, is due to a more effective chemical defence against epiphyte colonisation. A field survey of the distribution of the common fouling organism Balanus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 36 publications
5
63
1
Order By: Relevance
“…For example, differences in the hardness of wood species have a selecting effect on organisms that can colonise these woods (Nair & Saraswathy 1971, Borges et al 2003. Floating algae may also produce substances that inhibit successful establishment of potential rafters (e.g., Sieburth & Conover 1965, Wikström & Pavia 2004. Calder (1995) found that some hydroid species occurred abundantly on Sargassum fluitans but not on S. natans and vice versa.…”
Section: Effect Of Substratum Characteristics On Raftersmentioning
confidence: 99%
“…For example, differences in the hardness of wood species have a selecting effect on organisms that can colonise these woods (Nair & Saraswathy 1971, Borges et al 2003. Floating algae may also produce substances that inhibit successful establishment of potential rafters (e.g., Sieburth & Conover 1965, Wikström & Pavia 2004. Calder (1995) found that some hydroid species occurred abundantly on Sargassum fluitans but not on S. natans and vice versa.…”
Section: Effect Of Substratum Characteristics On Raftersmentioning
confidence: 99%
“…Wikström & Pavia (2004) found chemical inhibition of epiphytes by Fucus vesiculosus, and Grateloupia has been shown to exhibit antifouling properties (Hellio et al 2004, Paul et al 2006). This may explain the low number of species that settled directly on the hosts' tissues, especially Grateloupia, as most epiphyte species associated with Grateloupia grew on its dominant epiphyte, Neosiphonia harveyi.…”
Section: Temporal and Habitat Differences In Epiphyte Communitiesmentioning
confidence: 99%
“…They are suggested to have multiple ecological roles: some phlorotannins act as chemical defenses against herbivory (e.g., Steinberg, 1988;Targett and Arnold, 1998;Arnold and Targett, 2000;Pavia and Toth, 2000a) and as antifouling substances (Sieburth and Conover, 1965;Wikström and Pavia, 2004), although the evidence for this function is equivocal (Jennings and Steinberg, 1997). Concentrations of phlorotannins show phenotypic plasticity in response to environmental parameters, such as salinity, nutrient and light availability, ultraviolet irradiation, and intensity of herbivory (Yates and Peckol, 1993;Peckol et al, 1996;Pavia et al, 1997;Pavia and Toth, 2000b;Honkanen et al, 2002;Swanson and Druehl, 2002).…”
Section: Introductionmentioning
confidence: 99%